Dancing robots: aesthetic engagement is shaped by stimulus and knowledge cues to human animacy - Darda, Kohinoor M.; Maiwald, Aaron; Raghuram, Tanvi; Cross, Emily S. (Frontiers in Human Neuroscience, 2024)
An increasing presence of artificial intelligence (AI) and robots in the realm of art is moulding the aesthetic identity of the new-age consumer of art. Various questions arise with this development: do cues to the humanness of the origin of an artwork or artist influence our aesthetic preferences? Across two experiments, we investigated how the perception and appreciation of dance is influenced by cues to human animacy by manipulating (1) "agent form" (human-like or robot-like dancer); (2) belief about the source of the movement (human motion capture or computer animation); (3) the source of choreography (human-or computergenerated); and (4) belief about the source of choreography (believe a choreography is humanor computer-generated). Results pointed toward agent congruence -robot agents were preferred when the source of movement was thought to be computer animation (Experiment 1) and when the source of choreography was believed to be computer-generated (Experiment 2).Choreographies believed to be human-generated were preferred (Experiment 2) but participants could not accurately identify the actual source of choreography (Experiment 1). These results persisted above and beyond the effects of age, dance expertise, technological expertise, attitudes toward AI, and how familiar, complex, evocative, technically competent, or reproducible the dance was perceived to be. Dance expertise, technological expertise and attitudes toward AI independently impacted aesthetic judgments. Our findings provide valuable insights to the design and development of robotic dance by identifying the features of a dance choreography and audience characteristics that influence its aesthetic engagement.Additionally, along with creating more refined creative productions by using AI in a dancemaker's toolkit, shaping people's perceptions will be just as crucial for its reception and for better engagement.